The Teacher’s Efforts in Solving Students’ Writing Problems - Elsa Trisna Dewi; Bukhari Daud; Cairina Nasir (Research in English and Education Journal, 2017)
As one of language skills that is learned in schools in the context of teaching English as a foreign language in Indonesia, writing skill has been learned at the level of senior high school. Additionally, the problems in this study were the problems in writing as faced by EFL students. This research was intended to describe the difficulties in writing faced by students, and the efforts to overcome these problems that given by teacher. To collect the data, the writer conducted a descriptive qualitative research at SMA Negeri 3 Banda Aceh. Twenty-five students in XI IPA 6, twenty-four students in XI IPS 1 and two English teachers participated in this study. To conduct this study, the writer used questionnaire and interview. The result of this research shows that the difficulties faced by the EFL students in writing were lack of vocabulary, lack of ideas, grammar, content, organize idea, idiomatic expression and spelling. Therefore, there are some efforts were given,namely; learning more about grammar, memorizing the vocabulary, and motivate the students to practice their writing, and grouping students.